Urban novel ecosystems as affective landscapes - Collier, Marcus (My University, 2024)
Intertwined within a patchwork of different types of land use and land cover, novel ecosystems are urban ecosystems that have no historical analogues and contain novel species assemblages. Some researchers and practitioners in the field of conservation and restoration regard urban novel ecosystems unworthy of concern, while other groups call for their preservation due to the rate of biodiversity loss in cities and limited access to nature among some social groups. However, very little is known about how people perceive novel ecosystems (such as informal green spaces, post-industrial or derelict land sites awaiting redevelopment, brownfield sites, vacant lots, interstitial or gap spaces) which are often characterised by assemblages of wild, spontaneous, and overgrown vegetation, but also remanent or derelict urban infrastructure in cities. This paper addresses this gap by firstly asking how people percieve assemblages of wild-looking vegetation and urban infrastructure often found in novel ecosystems and how our affective and aesthetic responses to these ecosystems affects our attitudes towards wildness in cities. To begin to unpack this question, we obtain data from a series of exploratory workshops held in four cities in the global north where we asked people ‘what is urban nature?’ Our findings suggest that value judgements that people ascribe to novel ecosystems are often deeply polarised, but they are influenced by different ecological and urban conditions that people encounter within them. However, some negative perceptions about novel ecosystems may be mediated by situational cues; these situational cues could have important implications for rewilding and restoration programmes that aim to reconnect urban communities with nature through socio-ecological stewardship. To conclude, areas for further research that could improve our understanding of the social values of novel ecosystems in cities and the influence that these ecosystems may have on affective encounters with urban nature are proposed.
PUBLISHED
Intertwined within a patchwork of different types of land use and land cover, novel ecosystems are urban ecosystems that have no historical analogues and contain novel species assemblages. Some researchers and practitioners in the field of conservation and restoration regard urban novel ecosystems unworthy of concern, while other groups call for their preservation due to the rate of biodiversity loss in cities and limited access to nature among some social groups. However, very little is known about how people perceive novel ecosystems (such as informal green spaces, post-industrial or derelict land sites awaiting redevelopment, brownfield sites, vacant lots, interstitial or gap spaces) which are often characterised by assemblages of wild, spontaneous, and overgrown vegetation, but also remanent or derelict urban infrastructure in cities. This paper addresses this gap by firstly asking how people percieve assemblages of wild-looking vegetation and urban infrastructure often found in novel ecosystems and how our affective and aesthetic responses to these ecosystems affects our attitudes towards wildness in cities. To begin to unpack this question, we obtain data from a series of exploratory workshops held in four cities in the global north where we asked people `what is urban nature? Our findings suggest that value judgements that people ascribe to novel ecosystems are often deeply polarised, but they are influenced by different ecological and urban conditions that people encounter within them. However, some negative perceptions about novel ecosystems may be mediated by situational cues; these situational cues could have important implications for rewilding and restoration programmes that aim to reconnect urban communities with nature through socio-ecological stewardship. To conclude, areas for further research that could improve our understanding of the social values of novel ecosystems in cities and the influence that these ecosystems may have on affective encounters with urban nature are proposed.
Keywords: Novel ecosystems, Societal perception, Photo-elicitation, Affective landscapes; Inclusive Society; Smart & Sustainable Planet; Affective Landscapes; NOVEL ECOSYSTEMS; Photo-elicitation; Societal perception; Community; Environment and housing; Policy; Social participation